Ampliación del sistema de agua potable, y estudio del alcantarillado sanitario y planta de tratamiento de la lotización Marsella de la "R" perteneciente al cantón Santa Rosa de la provincia de El Oro. - Soto Blacio, Diego Patricio (2015)
In 1990 50.852 inhabitants were registered, increasing to 69,036 in 2001. The city of Santa Rosa Canton represents 0.5% of the population of Ecuador and 11% in the province of El Oro. According to the National Institute of Statistics and Census, INEC, the population of the canton is increased in absolute terms both in urban and rural areas. Approximately eight out of ten people live in Santa Rosa, the cantonal head; in smaller percentages, followed by the rural parishes of La Victoria and Bellavista. By direct observation and dialogue with the current inhabitants of this sector was determined that the population of this community is plagued by endemic problems affecting factor in the health of people and having a clear criterion based on the problem as described above, fortuitous consider the project, obtaining as profit decreased gastrointestinal diseases that are caused by infectious agents. Diseases are cured with medical treatment and traditional medicine. Increased risk diseases are made meet in the parish Medical Center and the Hospital de Santa Rosa. Santa Rosa is a canton gradually with struggle and effort has gone up, but has failed to emerge completely from lack of interest and financial support from the authorities, it is for this reason that still has many needs based to lead a good quality of life, where the bottom line has always been to have a quality basic services as it is a good supply of drinking water, sanitary sewer system which does not collapse in times of winter. (Wikipedia)